Too vulnerable to resist: Problematic use of dating apps associated with social appearance anxiety, social interaction anxiety, and rejection sensitivity - Huang, Yi-Ting; Gong, An-Di (Computers in human behavior, 2025)
Dating apps have become a prevalent method for young adults to build relationships. Although young adults with psychosocial vulnerabilities do benefit from dating apps, there remains the potential for problematic use. This study applied structural equation modeling to a sample of 5427 Taiwanese participants (mean age of 27.39 ± 4.51) collected using a cross-sectional online questionnaire. We found that social appearance anxiety, social interaction anxiety, and rejection sensitivity positively predicted the perceived benefits of digital communication (i.e., building interpersonal connections and control over self-presentation). Furthermore, we found a positive correlation between the perceived benefits of digital communication and a preference for online social interaction via dating apps. In addition, social appearance anxiety and social interaction anxiety positively predicted rejection sensitivity; social appearance anxiety, social interaction anxiety, and rejection sensitivity were positively correlated with the problematic use of dating apps; and rejection sensitivity mediated the relationship between social appearance anxiety, social interaction anxiety, and problematic use of dating apps. Exploring the dual psychological outcomes of dating app use revealed new findings related to dating app use among young adults and offered recommendations on effectively leveraging digital communication to foster beneficial interpersonal relationships. •Social appearance and interaction anxiety led to rejection sensitivity.•Psychosocial vulnerabilities predicted the perceived benefits of digital communication via dating apps.•Perceived benefits of digital communication driven a preference for online dating interactions.•Psychosocial vulnerabilities are linked to problematic dating app use.•Rejection sensitivity mediated between social anxiety and problematic use of dating apps.